Use of Mixed Dyes in Photogalvanic Cell for Solar Energy Conversion and Storage: EDTA-Toluidine Blue and Azur-B System - LAL, CHHAGAN; YADAV, SAROJ (Asian Journal of Chemistry, 2010)
Photogalvanic effect was studied in photogalvanic cell containing EDTA as reductant, Toluidine blue and Azur-B as photosensizer. The photopotential and photocurrent generated by this system were 802.0 mV and 40.0 μA, respectively. The observed conversion efficiency was 0.0708 % and the maximum output of cell was 32.08 μW. The photogalvanic cell can be used for 2 h in dark. The effects of different parameters on electrical output of the cell were observed and a mechanism has also been proposed for the generation of photocurrent in photogalvanic cell.